Motivations for Police Support of Domestic Violence Response Team Implementation With Advocates - Johnson, Laura (Violence against women, 2021)
In New Jersey, collaboration between police departments and advocates from domestic violence organizations is mandated by state policy, which requires law enforcement agencies to participate in domestic violence response teams (DVRTs). The purpose of this study is to examine factors that motivate police officers to implement DVRT. Twenty-four semi-structured interviews were conducted with DVRT coordinators and domestic violence liaison police officers. Findings suggest that police motivation for implementing the intervention is often influenced by perceived benefits to police response and investigation, perceived benefits to victims, the need to comply with mandates, and recognition of domestic violence as a serious crime.